Teachers' Strategies in Dealing with High Achievers in the Government Secondary Schools from the Teachers and Principals Perspectives - Fatema Jameel Sous (My University, 2010)
This study aimed at determining the level to which teachers practice strategies with academic achievers in secondary governmental schools from the teachers` and principals` points of view.It also aimed at evaluating the effect of some variables related to teachers' (gender, qualifications, experience, specialization, and training courses) on their practice of strategies in dealing with academic achievers, and knowing the effect of some variables related to principals' (gender, qualification , and experience) on evaluating the level to which such strategies are used by teachers. Furthermore, this study aimed at determining the obstacles that face the teachers when using strategies of dealing with academic achievers, and finding out the relationship between those strategies and the total degree. To achieve the aims of the study, the researcher developed and designed a questionnaire of some variables consisting of (56) items represented in four domains: protective strategy, constructive strategy and individuality strategy, and strategy of group dynamics. The sample consisted of (352) teachers and (105) principals. The collected data was analyzed by using (SPSS)statistical program. Results indicated that the level of using strategies to deal with academic achievers was intermediate up to extremely high level from teachers` and principals' points of view. Also, the results indicated significant differences due to gender in favor of male teachers. Similarly, the results indicated a significant difference due to the variable of training courses.No significant differences were found due to qualifications, years of experience and specialization for teachers, or years of experience for principals. Evaluating teachers` strategies when dealing with academic achievers, the researcher found that the main obstacles that face teachers when dealing with academic achievers are: time constrain, the difficulty and the amount of syllabus, and the lack of finance in governmental schools. Depending upon the results, the researcher recommended orientating the teachers with the skills required when dealing with academic achievers, eliminating the difficulties that face them, and adopting a particular clear plan from the side of the ministry of education to deal with academic achievers in secondary governmental schools.

هدفت الدراسة الحالية إلى تحديد درجة ممارسة المعلمين لاستراتيجيات التعامل مع المتفوقين دراسياً في المدارس الثانوية الحكومية من وجهة نظر المعلمين والمديرين. كما هدفت إلى معرفة أثر بعض المتغيرات المتعلقة بالمعلمين (الجنس، والمؤهل العلمي، وسنوات الخبرة، والتخصص، والدورات التدريبية) على ممارستهم لاستراتيجيات التعامل مع المتفوقين دراسياً، وكذلك معرفة أثر بعض المتغيرات المتعلقة بالمديرين (الجنس، والمؤهل العلمي، وسنوات الخبرة) على درجة تقديرهم لممارسة المعلمين لتلك الاستراتيجيات. كما سعت الدراسة إلى تحديد المعيقات التي تواجه المعلمين في استخدامهم لإستراتيجيات التعامل مع المتفوقين دراسيا، وإلى تبيان علاقة أبعاد تلك الاستراتيجيات والدرجة الكلية. ولتحقيق أهداف الدراسة قامت الباحثة بتطوير أداة للدراسة تضمنت بعض المتغيرات المتعلقة بالمعلمين والمديرين، و(56) عبارة موزعة على أربعة أبعاد هي: الإستراتيجية الوقائية، والإستراتيجية البنائية، وإستراتيجية التركيز على الفرد، وإستراتيجية دينامية الجماعة. وتكونت عينة الدراسة من(352) معلما و(105) مدير مدرسة. أظهرت النتائج باستخدام برنامج الرزمة الإحصائية للعلوم الاجتماعية(SPSS) أن درجة ممارسة المعلمين استراتيجيات التعامل مع المتفوقين دراسيا في المرحلة الثانوية من وجهة نظر المعلمين أنفسهم ومن وجهة نظر المديرين تتراوح بين متوسطة وكبيرة جدا، وبدرجة كبيرة جدا على الدرجة الكلية.كما أظهرت النتائج لما يخص استخدام المعلمين لاستراتيجيات التعامل مع المتفوقين دراسيا بوجود فرق دال إحصائيا يعزى لمتغير الجنس ولصالح المعلمين الذكور، وبوجود فرق دال إحصائيا يعزى لمتغير الدورات التدريبية للمعلمين ولصالح من حصلوا على دورات تدريبية، فيما لم تشر النتائج إلى وجود فروق دالة إحصائيا تعزى لمتغيرات المؤهل العلمي، وسنوات الخبرة، والتخصص للمعلمين، ولمتغيرات الجنس، والمؤهل العلمي، وسنوات الخبرة للمديرين من حيث تقديراتهم لاستراتيجيات المعلمين في التعامل مع المتفوقين دراسيا. وقد تبين من النتائج أن من أكثر المعيقات التي تواجه المعلمين في استخدامهم لاستراتيجيات التعامل مع المتفوقين دراسيا:هي ضيق وقت المعلم، وصعوبة المناهج وكبرها، وضعف الإمكانيات المادية للمدرسة. أوصت الباحثة بتأهيل المعلمين وتزويدهم بالمهارات التي تعزز من تعاملهم مع المتفوقين دراسيا.
استراتيجيات المعلمين في التعامل مع الطلبة المتفوقين دراسياً في المدارس الثانوية الحكومية من وجهة نظر المعلمين والمديرين